Incisional Surgical Site Infections After Mass and Layered Closure of Upper Abdominal Transverse Incisions: First Results of a Randomized Controlled Trial. Issue 5 (November 2021) - Grąt, Michał; Morawski, Marcin; Krasnodębski, Maciej; Borkowski, Jan; Krawczyk, Piotr; Grąt, Karolina; Stypułkowski, Jan; Maczkowski, Bartosz; Figiel, Wojciech; Lewandowski, Zbigniew; Kobryń, Konrad; Patkowski, Waldemar; et al.
Abstract : Objective: To compare the early results of mass and layered closure of upper abdominal transverse incisions. Summary of Background Data: Contrary to midline incisions, data on closure of transverse abdominal incisions are lacking. Methods: This is the first analysis of a randomized controlled trial primarily designed to compare mass with layered closure of transverse incisions with respect to incisional hernias. Patients undergoing laparotomy through upper abdominal transverse incisions were randomized to either mass or layered closure with continuous sutures. Incisional surgical site infection (incisional-SSI) was the primary end-point. Secondary end-points comprised suture-to-wound length ratio (SWLR), closure duration, and fascial dehiscence (clinicatrials.gov NCT03561727). Results: A total of 268 patients were randomized to either mass (n=134) or layered (n=134) closure. Incisional-SSIs occurred in 24 (17.9%) and 8 (6.0%) patients after mass and layered closure, respectively ( P =0.004), with crude odds ratio (OR) of 0.29 [95% confidence interval (95% CI) 0.13–0.67; P =0.004]. Layered technique was independently associated with fewer incisional-SSIs (OR: 0.29; 95% CI 0.12–0.69; P =0.005). The number needed to treat, absolute, and relative risk reduction for layered technique in reducing incisional-SSIs were 8.4 patients, 11.9%, and 66.5%, respectively. Dehiscence occurred in one (0.8%) patient after layered closure and in two (1.5%) patients after mass closure ( P >0.999). Median SWLR were 8.1 and 5.6 ( P <0.001) with median closure times of 27.5 and 25.0 minutes ( P =0.044) for layered and mass closures, respectively. Conclusions: Layered closure of upper abdominal transverse incisions should be preferred due to lower risk of incisional-SSIs and higher SWLR, despite clinically irrelevant longer duration. Abstract : Supplemental Digital Content is available in the text